Downslope movement of solifluction lobes in iceland: a tephrostratigraphic approach - Hirakawa Kazuomi (Department of Geography, Tokyo Metropolitan University, 1989)
Excavatins of the turf-banked solifluction lobe at 28 localities in Iceland have revealed dislocated and deformed volcanic ash layers composing solifluction lobes. Tephrostratigraphy and tephrochronology present much information about the rate and the mechanism of downslope movement of solifluction lobe which probably extends over the last 7,000 years. Downslope movement during the period between ca. 4,000 yBP and 2,000 yBP was faster than that in the last 900 years. The rate of downslope movement of solifluction lobe front is strongly associated with the gradients of slopes. However, environmental conditions, particularly those related to the existence of permafrost may have been favorable for the downslope movement. Concerning the mechanism of movement, the solifluction lobes have not moved as a slab slide, but as a viscous flows, because no shear plane was found.